Inspirational filmmaking to raise women’s voice and agency in the construction of assets for climate resilience in India - Kyle, Jordan; Kosec, Katrina; Narayanan, Sudha; Raghunathan, Kalyani (International Food Policy Research Institute, 2023)
Tusu lives in the village of Saradha in Mayurbhanj district of the eastern coastal state of Odisha in India, and recently constructed a farm pond on her land through the Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA). This important personal achievement might have gone mostly unnoticed—but through an inspirational video Tusu helped our team make, her story has reached over 6,500 rural Odisha women who now know what women like them can achieve through raising their voices to access key government programs.